Bulbophyllum contortum (Orchidaceae, Malaxideae), a new species from Yunnan, China - Zhou, Zhuang; Wu, Peng-Yu; Xu, Xiao-Wei; Zhao, Zhuang; Lin, Ya-Jun; Xu, Wan; Liu, Zhong-Jian (Phytotaxa, 2022)
A new orchid species, Bulbophyllum contortum (Malaxideae, Epidendroideae, Orchidaceae) from Zhenyuan, Yunnan, China, is described and illustrated here. Detailed morphological comparisons indicate that B. contortum is similar to B. lemnisactum and B. lemniscatoides, but it differs in the shape and size of pseudobulbs, inflorescence shape, flower colour and shape and size of the sepalar appendages.